Mechanism of Inverse Magnetoresistance in High-\(T_{a}\) Annealed MnNi/Co/Ag(Cu)/Py Spin Valves - Nguyen, Anh Tuan; Luong, Van Su; Hoang, Quoc Khanh; Tran, Thi Hoai Dung; Nguyen, Anh Tue (Communications in Physics, 2020)
The magnetic transport properties -- magnetoresistive (MR) effects of MnNi/Co/Ag(Cu)/\break Py pinned spin valve structures (SVs) prepared by rf sputtering method and annealed at \(T_{a} = 100\)°C - 500°C for 30 minutes in high vacuum (\(\sim 10^{ - 5}\) torr) are investigated. The received results show a change in the observed MR behaviors from a normal giant magnetoresistance effect to an inverse magnetoresistance effect after annealing at high temperatures, 300°C and 400°C, for these SVs. The origin and mechanism of the IMR behavior are analyzed and discussed. These results will suggest an ability to manufacture SV devices used the IMR effect for enhancing the application capacities for SV-sensor systems.